A series of organosilane liquid crystals and their application for the preparation of structurally colored organic–inorganic hybrid silica films. Issue 15 (8th December 2021) - Wei, Haohao; Wu, Limin; Sun, Wei; Xu, Tao; Liu, Wei; Li, Baozong; Li, Yi; Yang, Yonggang
ABSTRACT: A series of organosilane liquid crystals (OS n ) with different alkoxy chain lengths were synthesised. Both enantiotropic nematic and SmC phases were identified. With increasing the alkoxy chain length, SmC phase is feasible to be formed. Both the clearing points and SmC-nematic transition temperatures show odd-even effects. Small angle X-ray scattering characterisation indicated that the SmC phase of OS 6 showed a mono-layered structure. Cholesteric liquid crystal mixtures were prepared using OS 1, a bola -type organosilane (Bola-1) and a chiral dopant. After polycondensation under an acidic condition, structurally coloured organic–inorganic hybrid silica films were obtained. With increasing the weight ratio of Bola-1/OS 1, the reflection band of the film shifted to short wavelength. Abstract : uf0001